2016
DOI: 10.17738/ajes.2016.0017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative finite strain analysis of high-grade metamorphic rocks within the Mae Ping shear zone, western Thailand

Abstract: The NW trending Mae Ping shear zone exposes high-grade metamorphic rocks, the so called Lansang gneiss in the Tak region, western Thailand. The lithologies within the strike-slip zone mainly consist of orthogneisses and paragneisses. Using Fry's method for 2-dimensional strain analysis we find that the averaged finite strain ratio (R s ) of the XY-plane is R s = 1.35-1.69. Based on the kinematic vorticity analysis of the mylonitic gneisses in the shear zone, the kinematic vorticity number is W k = 0.8-1.0 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…These results fit well with the extrusion model in the SE Asia region (Lacassin et al, 1993(Lacassin et al, , 1997. The Three Pagodas shear zone is characterized by flow geometry similar to that recorded in the parallel northward Mae Ping shear zone (Ponmanee et al, 2016) with a smaller kinematic vorticity numbers (W k ) (Fig. 10).…”
Section: Kinematic Vorticity Numbersupporting
confidence: 80%
See 2 more Smart Citations
“…These results fit well with the extrusion model in the SE Asia region (Lacassin et al, 1993(Lacassin et al, , 1997. The Three Pagodas shear zone is characterized by flow geometry similar to that recorded in the parallel northward Mae Ping shear zone (Ponmanee et al, 2016) with a smaller kinematic vorticity numbers (W k ) (Fig. 10).…”
Section: Kinematic Vorticity Numbersupporting
confidence: 80%
“…However, the area where these strike-slip systems mechanically interact is still poorly documented. Many authors reported that the Mae Ping strike-slip zone is splayed to the Klaeng fault zone in eastern Thailand, and the Three Pagodas strike-slip zone is extended to the Ranong shear zone in the southern Thailand (Lacassin et al, 1993(Lacassin et al, , 1997Leloup et al, 1995;Gilley et al, 2003;Geard, 2008;Nantasin et al, 2012;Ridd, 2012;Ponmanee et al, 2016). In other geological interpretations (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mountain ranges in this area extend stretchy towards the Mae Ping fault, which gradually changes the orientation along the fault directly to the NW-SE direction. They have been recognized as a sinistral strike-slip fault [7,8]. In Shan-Thai terrane, its basement is occupied by Precambrian high-grade metamorphic and Middle or Upper Paleozoic rocks characterized by various grades of metamorphism overprinting sedimentary sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Rim region ages range [5]). Geologic map of Tak province (revised from [8,9]) reveals the location of the study area (in the red box).…”
Section: Introductionmentioning
confidence: 99%